Franciscan spirituality in Early Qing China: Pedro de la Piñuela’s Moxiang shengong (1694) and its Western sources - MEYNARD, Thierry; WANG, Qi (Journal of Research for Christianity in China (JRCC), 2025)
In the Sixteenth century, Franciscan spirituality started to disseminate widely all over the world. There has been a great deal of research on how Franciscan spirituality was transplanted in Latin America, but there is presently little research on East Asia. This paper shows how a Sixteenth century Franciscan treatise on meditation came to be translated into Chinese language and published in Canton in 1694. Based on textual analysis, it focuses on its Spanish sources and its efforts toward localization.